Knowledge and performance of the Iranian general population in the use of masks during the 2019 coronavirus - Seyedeh Tahereh Mirmolaei; Mehrnaz Geranmayeh; Hamid Salehiniya; Azam Mohammadi; Marzieh Ebrahimi (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The use of personal protective equipment (especially face masks) has increased in different communities amid the COVID-19 pandemic. Therefore, the present study aimed to assess knowledge and performance of Iranian general population in wearing face masks. MATERIALS AND METHODS: The present study is a cross-sectional study conducted using a valid and reliable questionnaire on 1843 eligible individuals. The questionnaires were shared by Link (www.porsall.com) in groups and social networks. Data were analyzed using SPSS (Version 24.0, SPSS Inc., Chicago, IL). RESULTS: The mean age of the participants was 42.84 years (standard deviation: 16.84). The majority had inadequate and low knowledge of masks (69.2%), nearly 30% had moderate (30.1%), and few had adequate and high knowledge of masks. The individuals' knowledge on when to wear a mask was also assessed and the results showed poor and low in 42.2%, 46.9% moderate and high performance in 10.7%. The participants' performance on how to properly wear a mask was also assessed and 12% showed poor, 69.3% showed moderate, and 18.7% showed high performance. Safe removal of masks was also assessed, and the results showed 52% low and poor, 27.6% moderate, and 20.3% high performance. A significant and direct correlation was found between the overall score knowledge and performance regarding use of masks (P < 0.001). CONCLUSION: The results showed poor to moderate knowledge and performance of majority of Iranian general population regarding the masks. Therefore, further effective training courses and action plans are needed in Iran given the importance of masks for the prevention of COVID-19, especially in public places. Educational package about how to use the mask and its benefits, through the media and health centers is recommended.